INNOVATIVE MARKETING AND RELATIONSHIP IMPROVING THE COMPANY'S REPUTATION: AN APPLIED STUDY AT COMPANY SOUTHERN GENERAL CEMENT / KUFA CEMENT FACTORY - Muhammad Najm Abd; Salima Hadi Musa; Prof. Dr. Hamed Kazem Meteb Al Shahbawi (Scholar Express Journal, 2023)
The research focused on innovative marketing(IM) as an independent variable with its dimensions of innovative promotion , innovation Price Innovation of the product, innovation of distribution , reputation of company as a dependent variable with its dimensions (quality of products The company, Quality of company's services, Company's leadership, the company's social responsibility, governance The company to determine the link of (IM) in company's reputation(CR) , research has been tested in a cement plant Kufa, study population reached (1132) workers, and (287) questionnaires were distributed, and 41 valid questionnaires were excluded, leaving (246) questionnaires that were actually used in statistical analysis, the percentage of sample representation from community was 25%. The hypotheses of correlation relationship, the statistical program (24. SPSS.V) was adopted to analyze the results, research reached to accept all hypotheses. Research reached a set of theoretical Therefore, applied conclusions, including that foundations of(IM) are closely related to rethinking , working to develop work of companies on an ongoing basis. Study was presented A set of recommendations, including development of (CR) among employees, because the employees possess it, which leads creating distinguished relationships between individuals in various fields, achieving methods of influencing others through (product quality, Quality of services, corporate social responsibility, leadership, governance) in organizational work environment , thus Stimulating human resource that contributes to increasing marketing and innovative processes
Keywords: company reputation; marketing; program